Implementation Of Pohlig-Hellman Algorithm And Steganography Combination Of First Of File (Fof) And End Of File (EOF) For File Security: Implementation Of Pohlig-Hellman Algorithm And Steganography Combination Of First Of File (Fof) And End Of File (EOF) For File Security - Reni Rahmadani; Hervei Desmon Hutahaean (Institute of Computer Science (IOCS), 2020)
The method of steganography First of File (FOF) has an additional lines at the beginning of image and End of File (EOF) method has an additional lines at the bottom of the image. To reduce the suspicion then FOF and EOF methods are combined produces stego image that has border at the top and bottom. To improve the security of message Pohlig-Hellman cryptographic algorithm is used. Pohlig-Hellman algorithm uses two keys (n and e) to process the encryption. Key n is a prime number algorithm tested with Lehmann. Key e have the legal conditions 1 <e <? (n) where ? (n) = n-1. Stego image produced has additional lines at the top and bottom of the image, it is because the ciphertext is inserted at the beginning and end of the image matrix. The result shows that the encryption process takes longer than the decryption process. Processing 129 character message encryption process takes 78 milliseconds and the decryption process takes just 16 milliseconds. Cover image of size 148 KB becomes 150 KB after embedding process of 1132 characters ciphertext.